Memorandum of understanding between Universiti Teknologi MARA and Asia Pacific University of Technology and Innovation / Fakulti Perubatan - Universiti Teknologi MARA, Fakulti Perubatan (Universiti Teknologi MARA (UiTM), 2021)
UiTM and Asia Pacific University of Technology and Innovation will endeavour to strengthen, promote and develop cooperation on the basis of equality and mutual benefit.